Rekonstruksi Manajemen Pengelolaan Pesantren Berbasis Social Entrepreneurship untuk Mendorong Kemandirian Pesantren (Studi Kasus Pondok Pesantren Sidogiri) - Setiawati, Riska Ayu; Tantriana, Deasy (Jurnal Manajemen dan Inovasi (MANOVA), 2024)
Pondok Pesatren are the oldest traditional educational institutions in transferring Islamic values to Indonesia. So when we see how the Salafiyah Islamic Boarding School Sidogiri Pasuruan, East Java, which is very consistent with its traditional pesantren education, was able to develop a modern business within the cooperative space of the Sidogiri Islamic Boarding School, and has even established three subsidiary companies within it, namely: PT. Sidogiri Mitra Utama, PT Sidogiri Mandiri Utama, PT. Sidogiri Pandu Utama. Based on the reality above, researchers want to understand the processing of Pondok Pesatrenin encouraging independence. This research intends to find answers regarding: first, how are the efforts to manage the Sidogiri Islamic Boarding School so that it can become an economically independent Islamic boarding school; second, how is the business analysis of the Sidogiri Islamic Boarding School Canvas Model. Based on its character, a qualitative approach was used in this study, through Peter L Barger's social construction theory analysis framework, while the research data was obtained from various sources through in-depth interviews, participant observation or observation, field notes. (fieldnotes) and documentation. This research resulted in the following results; the efforts of the Sidogiri Islamic Boarding School to reconstruct its management so that it can become an economically independent Islamic boarding school is carried out by running a business professionally. With the support of human resources for students who have good morals and a good work ethic, the management of the school unit. In the business model canvas of the Sidogori Islamic Boarding School, from all elements it is very clear that alumni play a very important role in expanding channels and customer relationships. SWOT analysis of social entrepreneurship-based Pondok Pesantren management at Pondok Pesantren Sidogiri can formulate future strategies for business management that will run well in the future One of the strategies proposed based on the SWOT analysis carried out is, open branches in various strategic locations, not only around the Pondok Pesantren Sidogiri.